Literature Review on Integrity Management of Subsea Pipelines Operating Beyond Design Life - Mohammed Riayadh (Collaborate, 2023)
Subsea pipelines are an important means of offshore oil and gas transportation. Subsea pipelines that operate beyond their design life can experience reduced performance and integrity due to factors such as corrosion, leaks, cracking, buckling, and scour. Subsea pipeline integrity management aims to ensure that subsea pipelines can operate safely and efficiently throughout their life cycle. This article reviews literature related to integrity management of subsea pipelines operating beyond their design life, including concepts, methods, technology, and challenges faced. The results of the review show that integrity management of subsea pipelines operating beyond their design life requires a comprehensive, integrated, and adaptive approach, considering technical, economic, environmental, and social aspects. This article also provides recommendations for further research and development in this area.